Off-Label Medicine Use in Pediatric Inpatients: A Prospective Observational Study at a Tertiary Care Hospital in India - Mohd Masnoon Saiyed; Tarachand Lalwani; Devang Rana (International Journal of Pediatrics)
Background. In the absence of standard pediatric prescribing information, clinicians often use medicines in an off-label way. Many studies have been published across the globe reporting different rates of off-label use. There is currently no study based on Indian drug formulary. Methods. The prospective observational study included pediatric patients in ages between 0 and 12 years admitted in a tertiary care hospital. Off-label use was assessed using the National Formulary of India (NFI). Predictors of off-label use were determined by logistic regression. Results. Of the 1645 medications prescribed, 1152 (70%) were off-label based on 14 possible off-label categories. Off-label medicines were mainly due to dose difference and use in restricted age limits as indicated in NFI. Respiratory medicines (82%), anti-infectives (73%), and nervous system medicines (53%) had higher off-label use. Important predictors of off-label prescribing were pediatric patients in age of 0 to 2 years (OR 1.68, 95% CI; P<0.001) and hospital stay of six to 10 days (OR 1.91, 95% CI; P<0.001). Conclusion. Off-label prescribing is common among pediatric patients. There is need to generate more quality data on the safety and efficacy of off-label medicines to rationalize pediatric pharmacotherapy.